An Observational Study of the Behaviour of Captive Rehabilitant Sun Bears (Helarctos malayanus). Issue 2 (3rd April 2021) - Forbes, Giverny; Crudge, Brian; Lewis, Kate; Officer, Kirsty; Descovich, Kris
ABSTRACT: Rehabilitant Malayan sun bears often remain in captivity for long periods of time and may experience significant welfare challenges including disability and persistent lip lesions. This study aimed to investigate whether short-term observations of behavior such as oral stereotypies are useful as noninvasive indicators of lip lesion pain, and whether behavior differs between able-bodied and disabled bears. Observations were collected from 21 captive, rehabilitant Malayan sun bears, of both sexes, a range of ages, and with lip lesions ranging in severity. Some also had disabilities. Oral stereotypy frequency was unrelated to lip lesion severity (p > 0.05), and no relationships with other behaviors were found; however, visual disabilities had significant effects on behavior. For example, visually disabled bears walked more than able-bodied bears (p = 0.003) or those with physical disabilities (p = 0.01). Further research on the feeding behavior of bears suffering from lip lesions may elucidate other potential behavioral indicators of pain. Researching effects of visual disabilities in bears with a larger sample size is also recommended to determine generalizable impacts in affected individuals and resulting welfare implications.